Alternative Organic Spacers for More Efficient Perovskite Solar Cells Containing Ruddlesden–Popper Phases - Xi, Jun; Spanopoulos, Ioannis; Bang, Kijoon; Xu, Jie; Dong, Hua; Yang, Yingguo; Malliakas, Christos D; Hoffman, Justin M; Kanatzidis, Mercouri G; Wu, Zhaoxin (Journal of the American Chemical Society, 2020)
The halide perovskite Ruddlesden–Popper (RP) phases are a homologous layered subclass of solution-processable semiconductors that have aroused great attention, especially for developing long-term solar photovoltaics. They are defined as (A′)2(A) n−1Pb n X3n+1 (A′ = spacer cation, A = cage cation, and X = halide anion). The orientation control of low-temperature self-assembled thin films is a fundamental issue associated with the ability to control the charge carrier transport perpendicular to the substrate. Here we report new chemical derivatives designed from a molecular perspective using a novel spacer cation 3-phenyl-2-propenammonium (PPA) with conjugated backbone as a low-temperature strategy to assemble more efficient solar cells. First, we solved and refined the crystal structures of single crystals with the general formula (PPA)2(FA0.5MA0.5) n−1Pb n I3n+1 (n = 2 and 3, space group C2) using X-ray diffraction and then used the mixed halide (PPA)2(Cs0.05(FA0.88MA0.12)0.95) n−1Pb n (I0.88Br0.12)3n+1 analogues to achieve more efficient devices. While forming the RP phases, multiple hydrogen bonds between PPA and inorganic octahedra reinforce the layered structure. For films we observe that as the targeted layer thickness index increases from n = 2 to n = 4, a less horizontal preferred orientation of the inorganic layers is progressively realized along with an increased presence of high-n or 3D phases, with an improved flow of free charge carriers and vertical to substrate conductivity. Accordingly, we achieve an efficiency of 14.76% for planar p–i–n solar cells using PPA-RP perovskites, which retain 93.8 ± 0.25% efficiency with encapsulation after 600 h at 85 °C and 85% humidity (ISOS-D-3).